A 120 000-year record of sea ice in the North Atlantic? - Maffezzoli N.; Vallelonga P.; Edwards R.; Saiz-Lopez A.; Turetta C.; Astrid Kjaer H.; Barbante C.; Vinther B.; Spolaor A. (Climate of the Past, 2019)
Although it has been demonstrated that the speed and magnitude of the recent Arctic sea ice decline is unprecedented for the past 1450 years, few records are available to provide a paleoclimate context for Arctic sea ice extent. Bromine enrichment in ice cores has been suggested to indicate the extent of newly formed sea ice areas. Despite the similarities among sea ice indicators and ice core bromine enrichment records, uncertainties still exist regarding the quantitative linkages between bromine reactive chemistry and the first-year sea ice surfaces. Here we present a 120 000-year record of bromine enrichment from the RECAP (REnland ice CAP) ice core, coastal east Greenland, and interpret it as a record of first-year sea ice. We compare it to existing sea ice records from marine cores and tentatively reconstruct past sea ice conditions in the North Atlantic as far north as the Fram Strait (50-85° N). Our interpretation implies that during the last deglaciation, the transition from multi-year to first-year sea ice started at ~17.5 ka, synchronously with sea ice reductions observed in the eastern Nordic Seas and with the increase in North Atlantic ocean temperature. First-year sea ice reached its maximum at 12.4-11.8 ka during the Younger Dryas, after which open-water conditions started to dominate, consistent with sea ice records from the eastern Nordic Seas and the North Icelandic shelf. Our results show that over the last 120 000 years, multi-year sea ice extent was greatest during Marine Isotope Stage (MIS) 2 and possibly during MIS 4, with more extended first-year sea ice during MIS 3 and MIS 5. Sea ice extent during the Holocene (MIS 1) has been less than at any time in the last 120 000 years.